(untitled) (قضايا سياسية, 2023)
The water file in Iraq is considered the most sensitive file، due to the decline in water. Water does not return to a state of shortage، but rather as a result of weakness in rational and efficient administration، as well as the imbalance in water policies، which made Iraq unable to overcome the shortage and scarcity that occurred، so the state of political instability، divisions and agreement of a general philosophy In Iraq، something that prevented Donat as well as the role of climate and lack of rainfall، and poor water rationalization.